Exploring Junior High School Students’ Online Self-Regulation During the Covid-19 Pandemic in China (International Conference on Computers in Education, 2020)
This mixed-methods study explored junior high school students’ online self-regulation during the covid-19 pandemic in China. Total of 229 students in a junior high school were invited. Data were collected from Online Self-regulated English Learning questionnaire and eight open- ended questions. Firstly, the exploratory factor analysis was conducted to study the factorial structures of leaners’ online self-regulation. The quantitative results shown that learners’ online self- regulation involved five factors: goal setting, environment structuring, task strategies and time management, help seeking and self-evaluation. Secondly, the content analysis of eight open-ended questions was conducted to explore learners’ expectations for ideal online English language learning. The qualitative results indicated these five factors of online self-regulation played a critical role in learners’ ideal online English language learning. This study provided several implications for language teaching instructors on effective use of technologies. It also offered suggestions for designing more effective online English language courses for supporting learners’ online self- regulatory learning.